Volatility timing under low-volatility strategy - NEO, Poh Ling (Institutional Knowledge at Singapore Management University, 2019)
The authors devise a volatility timing strategy based on statistical tests on the slope of the volatility decile portfolio return profile. Superior performance is obtained, with a 30% increase in Sharpe ratio and an order of magnitude improvement on cumulated wealth. The profitability of the volatility timing strategy can be attributed to holding a diversified portfolio during bear markets, while holding a concentrated growth portfolio during bull markets.